A heteropolyacid catalyst, preparation method and application

The heteropolyacid catalyst with controlled particle size and increased surface area, prepared via a microemulsion method, addresses the limitations of existing catalysts by achieving high conversion and selectivity in the oxidation of isobutyraldehyde to methacrylic acid, ensuring long-term stability and cost-effectiveness.

CN118925763BActive Publication Date: 2024-12-24YANTAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411425716.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2024-12-24
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

Existing catalysts for the selective oxidation of isobutyraldehyde to methacrylic acid suffer from issues such as poor activity, selectivity, thermal stability, and rapid deactivation, leading to increased production costs and environmental impact.

Method used

A heteropolyacid catalyst with a specific composition (P a V b Mo 12 A c B d C e O f) is prepared using a microemulsion method, resulting in nanoscale particles with controlled size distribution and increased surface area, enhancing reaction activity and selectivity.

Benefits of technology

The catalyst achieves high isobutyraldehyde conversion rates (>99.3%) and methacrylic acid selectivity (>94.8%) with no significant deactivation after 200 hours, improving production efficiency and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the field of catalyst technology, and specifically relates to a heteropolyacid catalyst, a preparation method and an application. The present invention prepares the heteropolyacid catalyst by mixing a specific raw material ratio and adopting a special preparation method, and the heteropolyacid salt particles formed are at the nanometer level, which significantly improves the low-temperature reaction activity of the catalyst and the selectivity of the target product compared with the catalyst synthesized by the traditional coprecipitation method; the structural formula of the catalyst is P a V b Mo 12 A c B d C e O f The catalyst has a primary particle size of 5-15 nm and a specific surface area of ​​10-20 m 2 / g; under normal pressure, when the reaction temperature is 270℃, the catalyst has no obvious deactivation after 200h of reaction, the isobutyraldehyde conversion rate is ≤99.3%, and the methacrylic acid selectivity is ≤94.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a heteropolyacid catalyst, a preparation method and an application thereof. Background Art

[0002] Methyl methacrylate (MMA) occupies a vital position in the chemical industry. It is an extremely important chemical intermediate. Its main use is in the production of organic glass. The organic glass produced has many advantages such as high transparency and good weather resistance. In addition, MMA can also polymerize with other monomers to form copolymers. These copolymers can be widely used in the field of coating modifiers, which can significantly improve the performance of coatings; it also plays an important role in polyvinyl chloride modifiers, which can enhance the stability and durability of polyvinyl chloride; at the same time, it also has broad application prospects in the fields of medical polymer materials. At present, there are many methods for producing MMA, including acetone cyanohydrin method, isobutylene two-stage oxidation method, isobutyraldehyde oxidation method and ethylene method. Among these methods, isobutyraldehyde, as a by-product of the butanol unit, has a significant advantage of sufficient resources. However, its utilization methods are relatively limited. Considering from multiple perspectives such as environmental protection and economic technology, the production of MMA using isobutyraldehyde as a raw material undoubtedly has a good development prospect. When using isobutyraldehyde as a raw material to prepare MMA, a heteropolyacid salt is required as a catalyst. The catalyst has high activity. Although it can accelerate the reaction speed to a certain extent, it is also easy to cause peroxidation. Once the peroxidation reaction occurs, the yield of the product will be reduced, thereby affecting the production efficiency. In addition, the oxidation reaction itself is a highly exothermic reaction, which easily causes the loss of catalyst activity. Once the catalyst activity is lost, the catalyst needs to be replaced frequently, which not only increases the production cost, but also affects the overall economic benefits.

[0003] CN103945938B discloses a composition of Mo a P b V c Cu d Y e Z f O g The heteropolyacid salt catalyst (wherein: Y is selected from potassium, rubidium, cesium and thallium; Z is selected from antimony and ammonium) can be used for selective oxidation of methacrolein and isobutyraldehyde to prepare MAA. The active component of the catalyst is prepared by conventional coprecipitation method, which has the problems of relatively large particle size, easy particle agglomeration, and unsatisfactory exposure of active sites, thus affecting the catalytic activity; at the same time, during the reaction process, due to particle agglomeration and uneven structure, it is easily affected by external factors such as temperature, pressure, and corrosion of reactants, resulting in rapid catalyst deactivation.

[0004] CN112076786B discloses a method for preparing a catalyst for catalyzing isobutylaldehyde to prepare methacrylic acid, wherein the method uses an improved Stober method to prepare mesoporous SnO 2 -M x O y @SiO 2 The carrier (M = Ce, Cr, Ti or W) is used as a surfactant in the mesoporous SnO 2 -M x O y @SiO 2 The surface of the nanoparticles is covered with a thin layer of amorphous silicon dioxide, which is modified and hydrolyzed by tetraethyl orthosilicate (TEOS) and then impregnated with H 4 PMo 11 VO 40 The catalyst is prepared by loading it on a carrier. Although this method increases the specific surface area of ​​the catalyst due to the mesoporous structure and adds more active centers, the active component uses H 4 PMo 11 VO 40 Heteropolyacids are not as heat-resistant as heteropolyacid salts, resulting in poor heat resistance, easy structural collapse, and the problem of peroxidation.

[0005] Jia et al. reported on the research on heteropoly acid salt catalyst for one-step oxidation of isobutyraldehyde to methacrylic acid (Journal of Catalysis, 1996, 17(4):301-305). Specifically, the heteropoly acid salt catalyst was prepared by coprecipitation method and 31 The catalyst was characterized by P-MASNMR, XRD and IR, and it was determined that the catalyst had a Keggin structure molybdenum phosphate skeleton and the positions of various elements in it. At the same time, the catalytic performance of the catalyst for the oxidation reaction of isobutyraldehyde was investigated, and it was found that the Cs-containing heteropolyacid salt gave the highest yield of the target product methacrylic acid. The effect of the mass ratio of the heteropoly compound to the carrier SiC on the catalyst activity was also studied. However, the catalyst had the problems of poor stability and short life. In addition, the yield and selectivity of the product need to be further improved.

[0006] In summary, the existing catalysts have many deficiencies in the process of selective oxidation of isobutyraldehyde to prepare methacrylic acid. Therefore, it is urgent to prepare a catalyst with high activity, good selectivity, good thermal stability, safety and environmental protection. This will not only help improve production efficiency and reduce production costs, but also reduce the impact on the environment and promote the sustainable development of related industries. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a catalyst for selective oxidation of isobutyraldehyde to prepare methacrylic acid with high activity, good selectivity and good thermal stability and a preparation method thereof.

[0008] The object of the present invention can be achieved by the following measures: The present invention adopts a heteropolyacid catalyst prepared by a special preparation method to selectively oxidize isobutylaldehyde to prepare methacrylic acid, and the structural formula of the catalyst is P a V b Mo 12 A c B d C e O f , wherein: A is a mixture of one or more alkali metal elements, B is a mixture of one or more elements such as Fe, Co, Ni, Cu, Mn, Pb, Sn, Cr, etc., C is a mixture of one or more elements such as Ti, Sb, As, Ge, Si, Zr, Bi, and a, b, c, d, e, and f are the molar ratios of the required elements:

[0009] a=0.25-3;

[0010] b = 0.1-3;

[0011] c = 0.1-6;

[0012] d = 0.01-6;

[0013] e = 0.1-5;

[0014] f is the amount of oxygen atoms that satisfy the oxide valence state;

[0015] In the XRD spectrum of the catalyst, at 2θ=10.83 ° , 21.68 ° , 26.64 ° ,30.86 ° ,36.36 ° The characteristic diffraction peaks of P-Mo heteropoly acid salts appeared at the positions; the primary particle size of the catalyst was 5-15 nm, and the specific surface area was 10-20 m 2 / g; when the catalyst is used for selective oxidation of isobutyraldehyde to prepare methacrylic acid, the isobutyraldehyde conversion rate is ≤99.3%, the methacrylic acid selectivity is ≤94.8%, and no obvious deactivation of the catalyst is observed after the reaction is carried out for 200 hours;

[0016] Compared with the heteropolyacid catalyst prepared by the co-precipitation method in the prior art, the catalyst of the present invention has the characteristics of narrower and controllable particle size distribution, large specific surface area, etc., and thus has superior properties such as high activity and good selectivity.

[0017] The present invention also provides a method for preparing the above-mentioned heteropolyacid catalyst, the method comprising the following steps:

[0018] Step 1: Preparation of microemulsion I:

[0019] Add high-valent oxides of Mo and V and phosphoric acid to deionized water, stir evenly to form a solution, heat the solution under reflux for 8-20 hours at a temperature of 60-120° C. to obtain a red transparent heteropoly acid solution, and cool it to room temperature for use; slowly add the heteropoly acid solution to the organic phase under stirring at a stirring rate of 800-1600 r / min to form a stable microemulsion I;

[0020] Step 2: Preparation of microemulsion II:

[0021] Adding a compound containing A, a divalent metal compound containing B, and a high-valent metal compound containing C into deionized water, wherein the valence of the metal ion in the high-valent metal compound is ≥3, and stirring evenly to obtain a mixed salt solution; slowly adding the mixed salt solution into the organic phase under stirring at a stirring rate of 800-1600 r / min to form a stable microemulsion II;

[0022] Step 3: Preparation of heteropolyacid catalyst:

[0023] The microemulsion II is slowly added to the microemulsion I under stirring to obtain a slurry, and the stirring is continued for 30-300 minutes at a stirring rate of 800-1600 r / min. The slurry is filtered, dried, calcined at 300-500° C. for 2-8 hours, and pressed into tablets to obtain the heteropolyacid catalyst.

[0024] Further, in step 1, the high-valent oxide of Mo is MoO 3 NH 4 ) 2 MoO 4 、Na 2 MoO 4 One or a mixture of two or more of the above, the high-valent oxide of V is V 2 O 5 NH 4 VO 3 、NaVO 3 One or a mixture of two or more.

[0025] Furthermore, in step 1, the organic phase consists of an organic solvent, a surfactant, and a co-surfactant.

[0026] Furthermore, in step 2, the organic phase consists of an organic solvent, a surfactant, and a co-surfactant.

[0027] Furthermore, the organic solvent is a C5-C10 alkane or cycloalkane, the surfactant is an anionic surfactant, a cationic surfactant and a nonionic surfactant, and the co-surfactant is a fatty alcohol with a carbon chain of C3-C9.

[0028] Furthermore, the C5-C10 alkane or cycloalkane is one or a mixture of two or more selected from pentane, octane, cyclohexane, etc.; the anionic surfactant is any one or a mixture of two selected from sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, etc.; the cationic surfactant is any one or a mixture of two selected from trimethylhexadecylammonium bromide, trimethylhexadecylammonium chloride, etc.; the nonionic surfactant is any one or a mixture of two selected from polyoxyethylene ether, alkylphenol polyoxyethylene ether, etc.; the fatty alcohol with a carbon chain of C3-C9 is one or a mixture of two or more selected from n-hexanol, cyclohexanol, pentanol, etc.

[0029] Furthermore, in step 2, the compound containing A is one or a mixture of two or more salts of Na, K, and Ce, the divalent metal compound containing B is one or a mixture of two or more divalent salts or divalent metal oxides of Fe, Co, Ni, Cu, Mn, Pb, Sn, and Cr, and the high-valent metal compound containing C is one or a mixture of two or more high-valent salts or high-valent metal oxides of Ti, Sb, As, Ge, Si, Zr, and Bi, and the valence of the metal ions in the high-valent salts or high-valent metal oxides is ≥3.

[0030] The present invention also provides a method for preparing methacrylic acid by selectively oxidizing isobutylaldehyde using the above catalyst, wherein the catalyst is crushed into particles of 20-40 mesh, loaded into a fixed bed reactor, and a reaction gas is introduced, and the space velocity is set to 500-5000h -1 , the reaction pressure is 10-500 kPa, the reaction temperature is 100-400°C, and the catalytic reaction is carried out for 100-300 hours.

[0031] Furthermore, the reactor is a fixed bed reactor or a shell-and-tube reactor.

[0032] Furthermore, the reaction gas is isobutylaldehyde, air, N 2 , water vapor, wherein the volume fraction of isobutyraldehyde is 2-50%, the volume fraction of air is 25-85%, N 2 The volume fraction of carbon dioxide is 10-70%, and the volume fraction of water vapor is 10-50%.

[0033] The beneficial effects of the present invention are:

[0034] 1. The present invention adopts a special preparation method to prepare a heteropolyacid catalyst. First, phosphorus, molybdenum and vanadium salts are reacted to generate a phosphorus-molybdenum-vanadium heteropolyacid aqueous solution, which is then formed into an oil-in-water type microemulsion with an organic phase. At the same time, a mixed aqueous solution of metal salts and an organic phase form an oil-in-water type microemulsion. The two microemulsions are quickly mixed under stirring to form an oil-in-water type capsule, the inner core of which is a heteropolyacid salt. The catalyst prepared by the special preparation method unexpectedly obtains an oil-in-water type capsule with a narrow and controllable particle size distribution. The heteropolyacid salt particles formed are at the nanometer level, and the specific surface area is significantly increased compared with the catalyst synthesized by the traditional co-precipitation method. This microscopic characteristic significantly improves the low-temperature reaction activity of the catalyst, avoids the catalyst from being deactivated at high temperature, and thus improves the selectivity of the target product MAA.

[0035] 2. The special preparation method of the present invention makes the primary particles of the catalyst smaller, effectively shortens the diffusion distance of the reactants or products, reduces the chance of deep oxidation of the reaction products, and effectively improves the selectivity of the target product;

[0036] 3. The special preparation method of the present invention makes the primary particles of the heteropolyacid catalyst smaller and increases the contact area with the thermal conductor, which can effectively remove the reaction heat, overcome the shortcomings of poor thermal conductivity of the catalyst and easy decomposition of the heteropolyacid salt when heated, and extend the service life of the catalyst. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with examples, but the present invention is not limited to the following examples.

[0038] Examples 1-3 are catalysts prepared by the aforementioned special preparation method, and Comparative Examples 1 and 2 are catalysts prepared by the traditional co-precipitation method.

[0039] Example 1: Preparation of heteropolyacid catalyst A

[0040] Step 1: Preparation of microemulsion I:

[0041] Add 18 g of MoO into 100 mL of deionized water. 3 , 0.5g V 2 O 5 and 1.3g of 85% phosphoric acid, heated under reflux at 95°C for 10h to obtain a red transparent heteropoly acid solution, cooled to room temperature for use; weighed 200g of cyclohexane, added 1.5g of sodium dodecyl sulfate and 0.6g of butanol, stirred to form a transparent organic phase; slowly added the heteropoly acid solution to the organic phase under stirring to form a stable microemulsion I;

[0042] Step 2: Preparation of microemulsion II:

[0043] Add 5 g of Co(NO 3 )2 6H 2 O, 8 g of 50% Mn(NO 3 ) 2 Aqueous solution, 3 g of As 2 O 5 , 2g of KNO 3 , stirring evenly to obtain a mixed salt solution; weighing 250g of cyclohexane, adding 2.5g of sodium dodecyl sulfate and 1g of butanol, stirring to form a transparent organic phase; slowly adding the mixed salt solution to the organic phase under stirring to form a stable microemulsion II;

[0044] Step 3: Preparation of heteropolyacid catalyst A:

[0045] The microemulsion II was slowly added to the microemulsion I under stirring to obtain a red slurry, which was stirred for 60 min, filtered, dried, calcined at 400°C for 4 h, and pressed into tablets to obtain heteropolyacid catalyst A;

[0046] The composition of the heteropolyacid catalyst A is: 1.08 Mo 12 V 0.64 As 1.25 Co 1.65 Mn 2.15 K 1.90 O 48.18 ;

[0047] The primary particle size of the heteropolyacid catalyst A is 10.7 nm and the specific surface area is 12.5 m 2 / g.

[0048] Example 2: Preparation of heteropolyacid catalyst B

[0049] Step 1: Preparation of microemulsion I:

[0050] Add 20 g of MoO into 120 mL of deionized water. 3 , 1g of V 2 O 5 and 1.5 g of 85% phosphoric acid, heated under reflux at 89° C. for 10 h to obtain a red transparent heteropoly acid solution, which was cooled to room temperature for use; 200 g of cyclohexane was weighed, 2.5 g of trimethylhexadecylammonium bromide and 1 g of amyl alcohol were added, and stirred to form a transparent organic phase; the heteropoly acid solution was slowly added to the organic phase under stirring to form a stable microemulsion I;

[0051] Step 2: Preparation of microemulsion II:

[0052] Add 6 g of Fe(NO 3 ) 3 9H 2O, 5g of Ni(NO 3 ) 2 6H 2 O, 3g Sb 2 O 5 , 3g of CsNO 3 , stirring evenly to obtain a mixed salt solution; weighing 200 g of cyclohexane, adding 2.5 g of trimethyl hexadecyl ammonium bromide and 1.5 g of butanol, stirring to form a transparent organic phase; slowly adding the mixed salt solution to the organic phase under stirring to form a stable microemulsion II;

[0053] Step 3: Preparation of heteropolyacid catalyst B:

[0054] The microemulsion II was slowly added to the microemulsion I under stirring to obtain a blue slurry, which was stirred for 60 min, filtered, dried, calcined at 350°C for 4 h, and pressed into tablets to obtain the heteropolyacid catalyst B;

[0055] The composition of the heteropolyacid catalyst B is: 1.12 Mo 12 V 1.15 Sb 1.60 Fe 1.28 Ni 1.49 Cs 1.33 O 49.75 ;

[0056] The primary particle size of the heteropolyacid catalyst B is 9.8 nm and the specific surface area is 15.2 m 2 / g.

[0057] Example 3: Preparation of heteropolyacid catalyst C

[0058] Step 1: Preparation of microemulsion I:

[0059] Add 20 g of MoO into 150 mL of deionized water. 3 , 0.8g V 2 O 5 and 1.5g of 85% phosphoric acid, heated under reflux at 100°C for 10h to obtain a red transparent heteropoly acid solution, cooled to room temperature for use; weighed 200g of hexane, added 2.0g of polyoxyethylene ether and 1g of octanol, stirred to form a transparent organic phase; slowly added the heteropoly acid solution into the organic phase under stirring to form a stable microemulsion I;

[0060] Step 2: Preparation of microemulsion II:

[0061] Add 10 g of Fe(NO 3 ) 3 9H 2 O, 5 g Cu(NO3 ) 2 ·3H 2 O, 3g Sb 2 O 5 , 3g of KNO 3 , stirring evenly to obtain a mixed salt water solution; weighing 200g of hexane, adding 2g of polyoxyethylene ether and 1g of octanol, stirring to form a transparent organic phase; slowly adding the mixed salt water solution to the organic phase under stirring to form a stable microemulsion II.

[0062] Step 3: Preparation of heteropolyacid catalyst C:

[0063] Microemulsion II was added to microemulsion I under stirring to obtain a blue slurry, which was stirred for 60 min, filtered, dried, calcined at 450°C for 4 h, and pressed into tablets to obtain catalyst C.

[0064] The composition of the heteropolyacid catalyst C is: 1.12 Mo 12 V 0.92 Sb 1.60 Fe 2.14 Cu 1.79 K 2.57 O 51.39 ;

[0065] The primary particle size of the heteropolyacid catalyst C is 8.7 nm and the specific surface area is 15.8 m 2 / g.

[0066] Comparative Example 1: Preparation of heteropolyacid catalyst D

[0067] Add 18 g of MoO into 100 mL of deionized water. 3 , 0.5g V 2 O 5 and 1.3 g of 85% phosphoric acid, heated under reflux at 95 °C for 10 h to obtain a red transparent heteropoly acid solution, which was cooled to room temperature and recorded as solution I;

[0068] Add 5 g of Co(NO 3 ) 2 6H 2 O, 8 g of 50% Mn(NO 3 ) 2 Solution, 3 g As 2 O 5 , 2g of KNO 3 , stir evenly to obtain mixed salt water solution II;

[0069] The mixed salt solution II was slowly added to the solution I under stirring to obtain a red slurry, which was stirred for 60 min, filtered, dried, calcined at 400 °C for 4 h, and pressed into tablets to obtain catalyst D.

[0070] The composition of the heteropolyacid catalyst D is: 1.08 Mo 12 V 0.64 As 1.25 Co 1.65 Mn 2.15 K 1.90 O 48.18 ;

[0071] The primary particle size of the heteropolyacid catalyst D is 35.2 nm and the specific surface area is 6.7 m 2 / g.

[0072] Comparative Example 2: Preparation of heteropolyacid catalyst E

[0073] Add 20 g of MoO into 120 mL of deionized water. 3 , 1g of V 2 O 5 and 1.5 g of 85% phosphoric acid, heated under reflux at 89 °C for 10 h to obtain a red transparent heteropoly acid solution, which was cooled to room temperature and recorded as solution I;

[0074] Add 6 g of Fe(NO 3 ) 3 9H 2 O, 5g of Ni(NO 3 ) 2 6H 2 O, 3g Sb 2 O 5 , 3g of CsNO 3 , stir evenly to obtain mixed salt water solution II;

[0075] The mixed salt solution II was slowly added to the solution I under stirring to obtain a blue slurry, which was stirred for 60 minutes, then filtered, dried, calcined at 350° C. for 4 hours, and pressed into tablets to obtain catalyst E;

[0076] The composition of the heteropolyacid catalyst E is: 1.12 Mo 12 V 1.15 Sb 1.60 Fe 1.28 Ni 1.49 Cs 1.33 O 49.75 ;

[0077] The primary particle size of the heteropolyacid catalyst E is 33.2 nm and the specific surface area is 7.2 m 2 / g.

[0078] The catalytic reaction of selective oxidation of isobutyraldehyde to prepare methacrylic acid using the above heteropolyacid catalyst is specifically as follows: the above catalysts AE are crushed into 20-40 mesh particles, 10 mL of the catalyst is measured and loaded into a fixed bed reactor, and isobutyraldehyde, air, N 2 , water vapor, wherein the volume fraction of isobutyraldehyde is 5%, the volume fraction of air is 45%, N 2 The volume fraction of water vapor is 20%, the volume fraction of water vapor is 30%, and the air velocity is set to 1000h -1 , the reaction pressure was normal pressure, the reaction temperature was 270°C, and there was no obvious deactivation of the catalyst after the reaction was carried out for 200 hours. The tail of the product was connected to a gas chromatograph for automatic sampling and online detection of the product. The isobutyraldehyde conversion rate and methacrylic acid selectivity are recorded in Table 1.

[0079] Table 1 Catalyst reaction performance evaluation results

[0080]

[0081] As can be seen from Table 1, the heteropolyacid catalyst prepared by the special preparation method of the present invention is more active and has better product selectivity than the catalyst prepared by the traditional coprecipitation method; in addition, the catalyst of the present invention has no obvious signs of deactivation after the catalytic reaction continues for 200 hours, and has good stability. This is because the heteropolyacid catalyst prepared by the special preparation method of the present invention can obtain oil-in-water capsules with narrow and controllable particle size distribution during the preparation process, and the heteropolyacid salt particles formed are at the nanoscale level. Compared with the catalyst synthesized by the traditional coprecipitation method, its specific surface area is significantly increased. This microscopic characteristic greatly improves the low-temperature reaction activity of the catalyst, improves the selectivity of the target product MAA, and avoids the deactivation of the catalyst at high temperature, thereby extending the service life of the catalyst.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A heteropolyacid catalyst, characterized in that The structural formula of the catalyst is P a V b Mo 12 A c B d C e O f , wherein: A is a mixture of one or more alkali metal elements, B is a mixture of one or more Fe, Co, Ni, Cu, Mn, Cr elements, C is a mixture of one or more Sb, As, Bi elements, a, b, c, d, e, f are the molar ratios of the required elements: a=0.25-3; b=0.1-3; c=0.1-6; d=0.01-6; e=0.1-5; f is the amount of oxygen atoms that satisfy the oxide valence state; In the XRD spectrum of the catalyst, at 2θ=10.83 ° , 21.68 ° , 26.64 ° ,30.86 ° ,36.36 ° The characteristic diffraction peaks of P-Mo heteropoly acid salts appeared at the positions; the primary particle size of the catalyst was 5-15 nm, and the specific surface area was 10-20 m 2 / g; when the catalyst is used for selective oxidation of isobutyraldehyde to prepare methacrylic acid, the isobutyraldehyde conversion rate is ≤99.3%, the methacrylic acid selectivity is ≤94.8%, and no obvious deactivation of the catalyst is observed after the reaction is carried out for 200 hours; The preparation method of the heteropolyacid catalyst comprises the following steps: Step 1: Preparation of microemulsion I: Add high-valent oxides of Mo and V and phosphoric acid to deionized water, stir evenly to form a solution, heat the solution under reflux for 8-20h at a temperature of 60-120°C to obtain a red transparent heteropolyacid solution, and cool it to room temperature for use; slowly add the heteropolyacid solution into the organic phase under stirring at a stirring rate of 800-1600r / min to form a stable microemulsion I; wherein the high-valent oxide of Mo is one or a mixture of two or more of MoO3, (NH4)2MoO4, and Na2MoO4, and the high-valent oxide of V is one or a mixture of two or more of V2O5, NH4VO3, and NaVO3; the organic phase is composed of an organic solvent, a surfactant, and a co-surfactant, the organic solvent is a C5-C10 alkane or cycloalkane, the surfactant is an anionic surfactant, a cationic surfactant, or a non-ionic surfactant, and the co-surfactant is a fatty alcohol with a carbon chain of C3-C9; Step 2: Preparation of microemulsion II: Adding a compound containing A, a divalent metal compound containing B, and a high-valent metal compound containing C to deionized water, wherein the valence of the metal ion in the high-valent metal compound is ≥3, and stirring evenly to obtain a mixed salt solution; slowly adding the mixed salt solution to an organic phase under stirring at a stirring rate of 800-1600 r / min to form a stable microemulsion II; the organic phase is composed of an organic solvent, a surfactant, and a co-surfactant, wherein the organic solvent is a C5-C10 alkane or cycloalkane, the surfactant is an anionic surfactant, a cationic surfactant, or a non-ionic surfactant, and the co-surfactant is a fatty alcohol with a carbon chain of C3-C9; Step 3: Preparation of heteropolyacid catalyst: The microemulsion II is slowly added to the microemulsion I under stirring to obtain a slurry, and the stirring is continued for 30-300 minutes at a stirring rate of 800-1600 r / min. The slurry is filtered, dried, calcined at 300-500° C. for 2-8 hours, and pressed into tablets to obtain the heteropolyacid catalyst.

2. A method for preparing the heteropolyacid catalyst according to claim 1, characterized in that: The preparation method comprises the following steps: Step 1: Preparation of microemulsion I: Add high-valent oxides of Mo and V and phosphoric acid to deionized water, stir evenly to form a solution, heat the solution under reflux for 8-20h at a temperature of 60-120°C to obtain a red transparent heteropolyacid solution, and cool it to room temperature for use; slowly add the heteropolyacid solution into the organic phase under stirring at a stirring rate of 800-1600r / min to form a stable microemulsion I; wherein the high-valent oxide of Mo is one or a mixture of two or more of MoO3, (NH4)2MoO4, and Na2MoO4, and the high-valent oxide of V is one or a mixture of two or more of V2O5, NH4VO3, and NaVO3; the organic phase is composed of an organic solvent, a surfactant, and a co-surfactant, the organic solvent is a C5-C10 alkane or cycloalkane, the surfactant is an anionic surfactant, a cationic surfactant, or a non-ionic surfactant, and the co-surfactant is a fatty alcohol with a carbon chain of C3-C9; Step 2: Preparation of microemulsion II: Adding a compound containing A, a divalent metal compound containing B, and a high-valent metal compound containing C to deionized water, wherein the valence of the metal ion in the high-valent metal compound is ≥3, and stirring evenly to obtain a mixed salt solution; slowly adding the mixed salt solution to an organic phase under stirring at a stirring rate of 800-1600 r / min to form a stable microemulsion II; the organic phase is composed of an organic solvent, a surfactant, and a co-surfactant, wherein the organic solvent is a C5-C10 alkane or cycloalkane, the surfactant is an anionic surfactant, a cationic surfactant, or a non-ionic surfactant, and the co-surfactant is a fatty alcohol with a carbon chain of C3-C9; Step 3: Preparation of heteropolyacid catalyst: The microemulsion II is slowly added to the microemulsion I under stirring to obtain a slurry, and the stirring is continued for 30-300 minutes at a stirring rate of 800-1600 r / min. The slurry is filtered, dried, calcined at 300-500° C. for 2-8 hours, and pressed into tablets to obtain the heteropolyacid catalyst.

3. The method for preparing a heteropolyacid catalyst according to claim 2, characterized in that: The C5-C10 alkane or cycloalkane is one or a mixture of two or more of pentane, octane, and cyclohexane; the anionic surfactant is any one or a mixture of two of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the cationic surfactant is any one or a mixture of two of trimethylhexadecylammonium bromide and trimethylhexadecylammonium chloride; the nonionic surfactant is any one or a mixture of two of polyoxyethylene ether and alkylphenol polyoxyethylene ether; the fatty alcohol with a carbon chain of C3-C9 is one or a mixture of two or more of n-hexanol, cyclohexanol, and pentanol.

4. The method for preparing a heteropolyacid catalyst according to claim 2, characterized in that: In step 2, the compound containing A is one or a mixture of two of the salts of Na and K, the divalent metal compound containing B is one or a mixture of two or more of the divalent salts or divalent metal oxides of Fe, Co, Ni, Cu, Mn, and Cr, and the high-valent metal compound containing C is one or a mixture of two or more of the high-valent salts or high-valent metal oxides of Sb, As, and Bi, and the valence of the metal ions in the high-valent salts or high-valent metal oxides is ≥3.

5. A method for preparing methacrylic acid by selectively oxidizing isobutyraldehyde using the heteropolyacid catalyst according to claim 1, characterized in that: The catalyst was crushed into 20-40 mesh particles, loaded into a fixed bed reactor, and the reaction gas was introduced at a space velocity of 500-5000 h -1 , the reaction pressure is 10-500 kPa, the reaction temperature is 100-400°C, and the catalytic reaction is carried out for 100-300 hours.

6. The method for preparing methacrylic acid by selectively oxidizing isobutyraldehyde using the heteropolyacid catalyst according to claim 5, characterized in that: The reaction gas is a mixed gas of isobutyraldehyde, air, N2 and water vapor, wherein the volume fraction of isobutyraldehyde is 2-50%, the volume fraction of air is 25-85%, the volume fraction of N2 is 10-70% and the volume fraction of water vapor is 10-50%.